PEMANFAATAN MEDIA PEMBELAJARAN ICT DALAM MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS PADA SISWA KELAS VIII-3 SMP NEGERI 9 TEBING TINGGI - Sri Mulyani (Universitas Negeri Medan, 2021)
The purpose of this research was to develop learning english subject based on ICT method.This study used a qualitative descriptive analysis technique.This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VIII-3 SMP Negeri 9 Tebing Tinggi which amounted to 38 students. The results showed that the method of the problem posing in English subject can improve student learning result characterized by increased mastery learning students, namely pre-cycle (60,52%), the first cycle (78,94%), cycle II (89,47 %) and complete learn the clasical equal to 89,47 %.Key word : ICT, English, Media